Fuzzy expert system package for the assessment of marine technology training programs - Abdul Hamid, Shamsul Effendy (2009)
There are many education and training packages in marine technologies around Malaysia. According to usual practice, it takes about four months for each training package to be assessed. So if it is not up to the minimum requirement, it is difficult for the provider or the students to make changes in the middle of the course. In this study, a fuzzy expert system was designed to provide an alternative way to assess a marine technology training program. This method incorporated fuzzy method with expert system and multi-criteria decision making technique. The entire process was programmed using FORTRAN and Microsoft Excel. Three marine programs from three different education providers were tested. Set of data inserted and the outcomes were analyzed. The results showed that the fuzzy expert system developed is reliable, user friendly and flexible.